Bakterijski artritis kolenskega sklepa po rekonstrukciji sprednje križne vezi - Sajovic, Matjaž (Zdravniški vestnik, 2008)
Septic arthritis of the knee is a rare complication after arthroscopic ACL reconstruction, and the most appropriate treatment is unclear. All case seriesreported so far, have been retrospective, and case numbers of septic arthritis have ranged from 4 to 11. Patients and From a consecutive case series of 1283 patients who underwent arthroscopic ACL reconmethods struction from January 1997 through May 2008, we report on 3 patients (0.23 %) with postoperative septic arthritis. All patients had acute infection (> 2 weeks), bacterial cultures showed Staphylococcus species in two patients, and in the last patient the bacterialSeptic arthritis of the knee is a rare complication after arthroscopic ACL reconstruction, and the most appropriate treatment is unclear. All case series reported so far, have been retrospective, and case numbers of septic arthritis have ranged from 4 to 11. Patients and From a consecutive case series of 1283 patients who underwent arthroscopic ACL reconmethods struction from January 1997 through May 2008, we report on 3 patients (0.23 %) with postoperative septic arthritis. All patients had acute infection (> 2 weeks), bacterial cultures showed Staphylococcus species in twopatients, and in the last patient the bacterial
Keywords: Anterior Cruciate Ligament; Arthritis, Infectious; Arthroscopy; Artritis infekcijski; Artroskopija; Bacterial Infections; Bakterijske infekcije; baktrijske infekcije; kirurško zdravljenje; Knee Injuries; Koleno, poškodbe; kolenski sklep; Pooperativne komplikacije; Postoperative Complications; Sprednji, križni ligament; Surgery; Treatment Outcome; Zdravljenje, izid